Frictional behaviour of the interface between concrete and rubber: Laboratory shear test and its elastoplastic model. (15th June 2018) - Zhang, Zhenyu; Wang, Shanyong; Feng, Jili
Highlights: Direct shear concrete specimens with/without rubber cushions were tested under loads. The post-peak shear strengths of interfaces without rubbers remain almost constant. Shear-slip at the interface with rubber is described by non-associated plastic model. Tests show thin rubber affected the mechanical response of the concrete lining. Abstract: This study focuses on the shear-friction behaviour of concrete interfaces (joints) with rubber between concrete segments or rings from the perspective of experiment and theoretical analysis. A number of direct shear concrete specimens with and without rubber cushions were tested under conditions of different normal loads. The shear test results of the concrete interfaces without rubber show that the slip or shear displacements can be divided into elastic and perfectly plastic phases. The post-peak shear strengths hold almost a constant with increasing shear slip, which can be described by the Coulomb frictional law. However, when concrete interface is pasted with rubber, the slip failure behaviour of the interfaces under pressure-shear loads is more appropriately characterized by hyperbolic failure criterion. The shear tests of the interfaces with rubber show that rubber materials significantly reduce the shear strength of the interfaces, which indicate that thin rubber can accommodate the mechanical response of the tunnel concrete lining, particularly by reducing the stress level of concrete segments surrounding joints due to the rubber material pasted to the joints. An elasto-plastic constitutive model for describing the three-dimensional mechanical behaviour of concrete joint with rubber is developed and also verified by means of the shear tests of concrete joints with rubber mentioned above. The predictions by the present interface model are well in agreement with the shear tests.